Studies on morphological structure, physical properties and colour strength of infrared dyed pineapple leaf fibre / Anis Nazahah Mohd Amin - Mohd Amin, Anis Nazahah (2023)
Pineapple is one of the most widely grown crops in Malaysia. It is usually consumed in fresh fruit selling and juice drinks. However, the widespread use of pineapple resulted in large agricultural waste of pineapple leaves that are poorly maintained by the authorities in Malaysia. Therefore, this study was carried out to overcome that problem by extracting the pineapple leaves into fibre and dyeing the extracted fibre due to their unique characteristic and abundance availability in Malaysia. At the same time, conventional exhaustion dyeing systems, which use large quantities of water, chemical, and energy, cause a lot of effluent loads to the environment. This study focused on to analyse the physical and morphological properties of pineapple leaf fibre (PALF) obtained from different extraction methods and investigating the colour shade and dyeing performance of dyed pineapple leaf fibre using infrared (IR) dyeing in comparison with exhaustion (EX) dyeing techniques. Mainly, a few dyeing concentrations (0.25%, 1.0%, 2.0% and 4.0%) and three primary colours of reactive dye (C.I. Reactive red 11, C.I. Reactive blue 5 and C.I. Reactive yellow 86) were used as a parameter which response to the yield of PALF’s colour shade towards dyeing. The extraction process of PALF was conducted using two methods, which involved manual and mechanical extraction methods. Different dyeing techniques were used to distinguish the dyeing performance of PALF.